Antioxidant and DNA damage protection potentials of selected phenolic acids. (March 2015) - Sevgi, Kemal; Tepe, Bektas; Sarikurkcu, Cengiz
Highlights: Antioxidant and DNA damage protection potential studied. Rosmarinic acid showed the best antioxidant activity. Protective activity of ferulic acid was excellent on DNA. Abstract: In this study, ten different phenolic acids (caffeic, chlorogenic, cinnamic, ferulic, gallic, p-hydroxybenzoic, protocatechuic, rosmarinic, syringic, and vanillic acids) were evaluated for their antioxidant and DNA damage protection potentials. Antioxidant activity was evaluated by using four different test systems named as β-carotene bleaching, DPPH free radical scavenging, reducing power and chelating effect. In all test systems, rosmarinic acid showed the maximum activity potential, while protocatechuic acid was determined as the weakest antioxidant in β-carotene bleaching, DPPH free radical scavenging, and chelating effect assays. Phenolic acids were also screened for their protective effects on pBR322 plasmid DNA against the mutagenic and toxic effects of UV and H2 O2 . Ferulic acid was found as the most active phytochemical among the others. Even at the lowest concentration value (0.002 mg/ml), ferulic acid protected all of the bands in the presence of H2 O2 and UV. It is followed by caffeic, rosmarinic, and vanillic acids. On the other hand, cinnamic acid (at 0.002 mg/ml), gallic acid (at 0.002 mg/ml), p-hydroxybenzoic acid (at 0.002 and 0.004 mg/ml), and protocatechuic acid (at 0.002 and 0.004 mg/ml) could not protect plasmid DNA.